'Transparent things, through which the Past Shines': Investigating Holograms in the Collection of the National Gallery of Australia†. Issue 3 (2nd July 2016) - Wise, Andrea
Abstract : The National Gallery of Australia (NGA) holds a varied and, from a conservation point of view, challenging, collection of new media, including holograms by artists such as Robyn Beeche, Shu-Min Lin, Paula Dawson, and Margaret Benyon. Few artists see the making of a hologram as an integral part of their practice. Paula Dawson and Margaret Benyon are exceptions. Both are pioneers in the area having made and used holograms for many years. While their subject matter and intent are quite different, both artists are attracted by the technical complexities of the media and both use holograms to blur the boundaries between reality and illusion. When works by these artists were requested for loan, it prompted an opportunity for investigation into the history and development of holograms and examination of particular and potential materials and techniques. This paper provides an overview of this information and presents some considerations for conservators working with holograms.